Analisis Asuhan Keperawatan Pada Pasien Efusi Pleura Dengan Gangguan Pemenuhan Kebutuhan Dasar Oksigenasi Menggunakan Intervensi Breathing Exercise - Nur Pratiwi, Dian Khafifa; Patima; Musdalifah; Hasnah (Alauddin Scientific Journal of Nursing, 2024)
Background: Basic human needs are the elements needed by humans in maintaining physiological and psychological balance, which aims to maintain life and health. Certain medical conditions can hinder the process of oxygenation in the body. These conditions include disorders of the respiratory and cardiovascular systems. One disease that occurs in the lungs is pleural effusion. In the treatment of pleural effusion, pharmacological therapy alone is not enough to relieve shortness of breath in some patients. One of the non-pharmacological therapies currently being developed is breathing exercise in an effort to treat complaints of shortness of breath in patients. Purpose :The purpose of this study was to find out the description of Nursing Care Analysis on Pleura Effusion Clients with Disorders of Fulfilling Basic Needs of Oxygenation Using Breathing Exercise Intervention at Dr. Wahidin Sudirohusodo General Hospital Makassar. Method: The research method used is a case study with data collection techniques through physical examination, interviews and observation. Results: some nursing problems can be resolved, and there are changes after the provision of nursing interventions is carried out Conclusion: giving breathing exercise interventions can help clients shortness of breath and optimize muscle work breathing, some of the formulated nursing problems can be resolved.